Uterine Artery Doppler Pulsatility Index in the First Trimester as a Forecaster of Pre-Eclampsia in Primary Gravida - Humayun, Pareesae Artemis; Aziz, Sadaf; Arif, Ayesha; Afsheen, Afeera; Arif, Nadia; Batool, Sadiqa (Pakistan Armed Forces Medical Journal, 2023)
Objective: To uncover a correlation between a high uterine artery pulsatility index on Doppler ultrasound and the early onset of pre-eclampsia to reduce maternal and fetal morbidity and mortality.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Gynecology and Obstetrics, Combined Military Hospital, Multan Pakistan, from Jun 2020 to Dec 2021.Methodology: After Ethical Approval and informed consent, the umbilical artery pulsatility (UAPI) of the patients was measured by a transabdominal scan(TAS) between 75 and 100 days. Raised UAPI was correlated with early onset preeclampsia.Results: One hundred and sixty pregnant women were included in the study, out of which 34(21.3%) women developed preeclampsia, and 126(78.8%) were normal patients. Maternal weight (p=0.001), maternal BMI (p=0.002), gestational age and weight at delivery (p=0.001), and uterine artery doppler pulsatility index (p=0.001) had statistically significant differences with pre-eclampsia and regular patients among the target population.Conclusion: First-trimester uterine artery pulsatility index on Doppler ultrasound is a beneficial technique to recognize the women by risk status and target them to prevent pre-eclampsia.